RUNOFF AND EROSION IN DIFFERENT (AGRO) CLIMATOLOGICAL ZONES OF LATIN AMERICA AND PROPOSALS FOR SOIL AND WATER CONSERVATION SCENARIOS - Donald Gabriels; Deyanira Lobo; Wouter Schiettecatte; Koen Verbist; Pedro Cisneros (Sociedade & Natureza)
Steeplands, when cleared from forests, are susceptible to erosion by rainfall and are prone toland degradation and desertification processes.The dominant factors affecting those erosion processes and hence the resulting runoff and soillosses are the aggressiveness of the rainfall during the successive plant growth stages, the soilcover-management, but also the topography (slope length and slope steepness). Depending onthe type of (agro) climatological zone, the runoff water should either be limited and controlled(excess of water) or should be enhanced and collected from the slope on the downslopecropping area if water is short (negative soil water balance).Examples are given of practical applications in Ecuador where alternative soil conservationscenarios are proposed in maize cultivation in small fields on steep slopes. Adding peas andbarley in the rotation of maize and beans resulted only in a slight decrease of the soil losses.Subdividing the fields into smaller parcels proved to give the best reduction in soil loss.Because the average slope steepness is high, erosion control measures such as contourploughing and strip cropping have only small effects.Erosion and its effect on productivity of a sorghum -livestock farming system are assessed onfour different areas in Venezuela with different levels of erosion. A Productivity Index (PI)and an Erosion Risk Index (ERI) were used to classify the lands for soil conservationpriorities and for alternative land uses. Intensive agriculture can be applied on slightly erodedsoil, whereas severely eroded soil can be used with special crops or agro-forestry. Semiintensiveagriculture is possible on moderately eroded soil.Reforestation of drylands in Chili requires understanding of the infiltration/runoff process inorder to determine dimensions of water harvesting systems. Infiltration processes in semi-aridregions of Chile were evaluated, using rainfall experiments and constant-head infiltrationmeasurements. Correlations between infiltration parameters and locally variablecharacteristics as soil structure, field slope and stoniness were investigated for six differentsites, aiming at improving the design and positioning of runoff collecting systems.